Transcriptional Regulators of T Helper 17 Cell Differentiation in Health and Autoimmune Diseases - Capone, Alessia; Volpe, Elisabetta (Frontiers in Immunology, 2020)
T helper (Th) 17 cells are a subtype of CD4 T lymphocytes characterized by the expression of retinoic acid-receptor (RAR)-related orphan receptor (ROR)γt transcription factor, encoded by gene Rorc. These cells are implicated in the pathology of autoimmune inflammatory disorders as well as in the clearance of extracellular infections. The main function of Th17 cells is the production of cytokine called interleukin (IL)-17A. This review highlights recent advances in mechanisms regulating transcription of IL-17A. In particular, we described the lineage defining transcription factor RORγt, and other factors that regulates transcription of Il17a or Rorc by interacting with RORγt or by binding their specific DNA regions, that may influence positively or negatively their expression. Moreover, we reported the eventual involvement of those factors in Th17-related diseases, such as multiple sclerosis, rheumatoid arthritis, psoriasis and Crohn’s disease, characterized by an exaggerated Th17 response. Finally, we discussed the potential new therapeutic approaches for Th17-related diseases targeting these transcription factors. The wide knowledge of transcriptional regulators of Th17 cells is crucial for the better understanding of the pathogenic role of these cells and for development of therapeutic strategies aimed at fighting Th17-related diseases.